Deleterious Effects of Epicardial Adipose Tissue Volume on Global Longitudinal Strain in Patients With Preserved Left Ventricular Ejection Fraction - Maimaituxun, Gulinu; Kusunose, Kenya; Yamada, Hirotsugu; Fukuda, Daiju; Yagi, Shusuke; Torii, Yuta; Yamada, Nao; Soeki, Takeshi; Masuzaki, Hiroaki; Sata, Masataka; Shimabukuro, Michio (Frontiers in Cardiovascular Medicine, 2021)
Background: It is known that epicardial adipose tissue (EAT) volume is linked to cardiac dysfunction. However, it is unclear whether EAT volume (EATV) is closely linked to abnormal LV strain. We examined the relationship between EATV and global longitudinal strain (GLS), global circumferential strain (GCS), and global radial strain (GRS) in patients with preserved LV function. Methods: Notably, 180 consecutive subjects (68 ± 12 years; 53% men) underwent 320-slice multi-detector computed tomography coronary angiography and were segregated into coronary artery disease (CAD)(≥ 1 coronary artery branch stenosis ≥ 50%) and non-CAD groups. GLS, GCS, and GRS were evaluated by 2-dimensional speckle tracking and patients with preserved left ventricular (LV) ejection fraction (LVEF) ≥ 50% were selected. Results: First, GLS, but not GRS and GCS, was lower in the high EATV group though the LVEF was comparable to the low EATV group. Frequency of GLS ≤ 18 was higher in the high EATV group. Second, multiple regression model showed that EATV, age, male sex, and CAD, were determinants of GLS. Third, the cutoff points of EATV were comparable (~116-117 mL) in both groups. The cutoff of EATV ≥ 116 showed a significant correlation with GLS ≤ 18 in overall subjects. Conclusions: Increasing EATV was independently associated with global longitudinal strain despite the preserved LVEF and lacking obstructive CAD. Our findings suggest an additional role of EAT on myocardial systolic function by impaired LV longitudinal strain.